Dynamic simulation, parameter optimization, and control of a reactive distillation column for production of isopropanol via propylene hydration - Feizi-Afshar, Bahareh (Array, 2021)
In this study, a reactive distillation column for production of isopropanol was investigated. Firstly, a dynamic model was developed for the process. The model of the process was then programmed, and the process simulated using a base case obtained from the literature. Results showed that distillate contained more than 58 mol% propylene-free isopropanol. In the next step, optimization of some operating variables was performed to maximize concentration of isopropanol in distillate with condenser temperature as constraint, which was considered to be above the freezing point of water. Several simulations were performed by changing operating parameters, and finally optimum isopropanol content in distillate was obtained above 58 mol%. Results of using classic controllers showed that PID controller had the best performance for both condenser temperature set-point tracking and disturbance rejection.